HUBUNGAN MANAJEMEN DIRI DAN SELF EFFICACY DENGAN KUALITAS HIDUP PASIEN DIABETES MELITUS - Syirli Anggriani; Musliha Musliha; Kodariyah Kodariyah (Poltekkes Kemenkes Jambi, 2026)
Background: Complications of diabetes mellitus (DM) negatively impact patients’ quality of life and increase morbidity. Self-efficacy plays an essential role in diabetes self-management. This study aimed to examine the association between self-management and self-efficacy with the quality of life of patients with DM. Methods: A quantitative analytic survey with a cross-sectional design was conducted among 123 DM patients at Puskesmas Simpang IV Sipin. Participants were selected using simple random sampling. Data on self-management, self-efficacy, and quality of life were analyzed using statistical tests with a significance level of p < 0.05. Results: Of the respondents, 61.8% demonstrated good self-management and 58.5% reported high self-efficacy, while 51.2% had a high quality of life. Statistical analysis showed a significant relationship between self-management and quality of life (p = 0.001) and between self-efficacy and quality of life (p < 0.001). Conclusion: Self-management and self-efficacy are significantly associated with the quality of life of DM patients. Strengthening interventions to improve these aspects may serve as effective preventive and promotive strategies in primary healthcare settings